Uji Mekanik Membran Kitosan Berbahan Dasar Cangkang Kepiting - Lestari, Indah; Prasetya, Dwi Sabda Budi; Pangga, Dewi (IKIP Mataram, 2018)
[Title: The Effect of Thinking Aloud Pair Problem Solving Learning Model Toward Student Physics Science Learning Outcomes]. This study aims to test mechanical on membrane composite membrane based crab shell and poly vinly Acetat (PVA). A mechanical test was performed to test the young modulus of the membrane in maintaining pore size using the